The Difficulty Factors of English Education Department Students in Translating English Text - Diadara Mega Nurcahyani; Erna Dwinata (LinguA-LiterA: Journal of English Language Teaching Learning and Literature, 2021)
This research concerns about translation difficulties faced by English Education Department students of Bhinneka PGRI University. There will be some objectives of the study that can be formulated as follows: 1) To know what types of difficulties factor faced by students in translating English text. 2)To analyze which kind of difficulties factor is the most often faced by the students. The method which is used in this research is the descriptive qualitative approach. The instrument of this research is a questionnaire. The result of this study shows that the highest percentage of students' difficulties in translating is on linguistics factor. It is concluded that the highest point of translating is the difficulties to understand the meaning of words that not find in the dictionary. It was obtained 69.23% of the total percentage. It was also found that students sometimes difficult to translate a long and complex sentence, they are about 69% of the students. And there still 2 aspects which obtain 69,23% included in linguistics factor. In conclusion, linguistics factors become the most frequent obstacles that arise.